Pengaruh Penggunaan Media Animasi terhadap Motivasi Belajar IPS - Sukasih Sukasih; Sunarti Sunarti (Proceedings Series on Social Sciences & Humanities, 2022)
This research takes the theme of learning media. This research was conducted in the fifth grade of SD Negeri Kalirejo, Bagelen, Purworejo. The purposes of this study are (1) to describe the social studies learning process by using animation media, (2) to find out how much students' learning motivation before and after using animation media, (3) to find out the effect of using animation media on students' social studies learning motivation. The design of this study uses a full experimental design (true experimental design) through pretest and posttest. The pretest and posttest were carried out in the same group. The subjects or population in this study were fifth grade students at SD Negeri Kalirejo, Bagelen, Purworejo, Academic Year 2020/2021. The data sampling technique was carried out by interview and observation questionnaires. While the data were analyzed descriptively and inferentially. The results of the research show that: (1) The use of animation media in social studies learning is carried out through the planning, implementation and evaluation stages. (2) There is an increase in students' learning motivation for social studies after using animation media compared to before using animation media from what was in the moderate category to the very good category. (3) There is an effect of using animation media on social studies learning motivation of fifth grade students at SD Negeri Kalirejo, Bagelen, Purworejo.